2008
DOI: 10.1682/jrrd.2007.08.0119
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for design of future cochlear implant electrode arrays: Electrode array stiffness, size,

Abstract: Abstract-The level of hearing rehabilitation enjoyed by cochlear implant (CI) recipients has increased dramatically since the introduction of these devices. This improvement is the result of continual development of these systems and the inclusion of subjects with less severe auditory pathology. Developments include advanced signal processing, higher stimulation rates, greater numbers of channels, and more efficient electrode arrays that are less likely to produce insertion damage. New directions in the applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
121
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(126 citation statements)
references
References 43 publications
0
121
0
1
Order By: Relevance
“…There are a number of variables related to hearing preservation that need to be clarified and investigated. These variables include electrode design, the use of hair cell protection, electrode insertion depth and the method of electrode insertion, which should be as atraumatic as possible [Ishii et al, 1995;Roland et al, 2005;Rebscher et al, 2008;Verbist et al, 2009]. Until recently, the electrode insertion speed and its impact on insertion characteristics has not been examined in detail, especially in the clinical setting [Majdani et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of variables related to hearing preservation that need to be clarified and investigated. These variables include electrode design, the use of hair cell protection, electrode insertion depth and the method of electrode insertion, which should be as atraumatic as possible [Ishii et al, 1995;Roland et al, 2005;Rebscher et al, 2008;Verbist et al, 2009]. Until recently, the electrode insertion speed and its impact on insertion characteristics has not been examined in detail, especially in the clinical setting [Majdani et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…In many cases this damage results in decreased coupling efficiency and inconsistent channel-to-channel performance. Analysis of the forces that affect the occurrence of trauma and the angle at which an electrode contacts tissue have identified two primary mechanisms of injury [121][122][123][124][125][126]. First, damage most frequently occurs as a straight electrode, or curved electrode held on a stylet, contacts the outer wall of the scala tympani as it spirals away from the round window or cochleostomy through which the electrode was inserted.…”
Section: A Design Goals For Intracochlear Electrodesmentioning
confidence: 99%
“…In our trials at UCSF surgeons have observed little resistance to insertion and were confident that the electrodes were implanted with little or no trauma. Particularly in cases with the Advanced Bionics HiFocusℱ electrode with positioner, subsequent dimensional analysis [127,149 ] and temporal bone evaluations indicate that many, or most, of these insertions exceeded the depth at which the electrode and positioner could be located without trauma. This disparity indicates that it is very difficult to sense the level of resistance that signals the initiation of injury with a large tapered electrode carrier.…”
Section: Insertion Trauma Depth and Electrode Designmentioning
confidence: 99%
“…Rebscher et al, 15 who tested the insertion damage in correlation to the stiffness of 8 different models of electrode arrays, showed that electrode arrays with proportionately greater stiffness in the vertical plane were less likely to produce severe trauma during insertion. Severe damage, defined as an electrode array dislocation from the scala tympani into the scala media or scala vestibuli, varied in straight electrodes from 0% to 37.5% and in spiral types from 0% to 38.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Electrode arrays designed to position stimulating contacts near the modiolus appear to operate with lower current thresholds than previous devices that were located closer to the lateral wall of the scala tympani. [15][16][17] The charge units of maximum comfortable loudness level of the 2 groups were compared to determine whether an electrode dislocation was associated with higher stimulus charges.…”
Section: Discussionmentioning
confidence: 99%